(rev.) Adam Daniel Rotfeld, Marcin Wojciechowski, W cieniu. 12 rozmów z Marcinem Wojciechowskim [In the Shadow. 12 Conversations with Marcin Wojciechowski], Agora SA, Warszawa 2012 - Muszyńska, Agata (The Copernicus Journal of Political Studies, 2018)
Full text: http://bazhum.muzhp.pl/czasopismo/589/?idno=14763